2012
DOI: 10.1097/meg.0b013e32834febef
|View full text |Cite
|
Sign up to set email alerts
|

The management of low-risk primary upper gastrointestinal haemorrhage in the community

Abstract: Patients presenting with a primary upper gastrointestinal haemorrhage aged below 70 years with a Glasgow Blatchford Score of 2 or less are at a low risk, and can be safely managed in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It was found to be safe as none of the patients received endoscopic therapy, blood transfusion or surgery for UGI bleeding. A GBS ≤ 2 supplemented with clinical criteria was used to select low-risk bleeders 14 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be safe as none of the patients received endoscopic therapy, blood transfusion or surgery for UGI bleeding. A GBS ≤ 2 supplemented with clinical criteria was used to select low-risk bleeders 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that these scores could be used to identify patients at very low risk who could be managed as outpatients. [12][13][14] Studies have also suggested that these scores could identify patients at higher risk who might require urgent endoscopy or management in high dependency or intensive care units. 15 16 Several studies have compared scores in their ability to predict various outcomes.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In this cohort of patients the 28 d mortality rate was 0 [43] . The GBS has been shown to be as good as the Rockall score in predicting the need for any intervention, namely the need for therapeutic endoscopy [41,42,[44][45][46][47] .…”
Section: The Importance Of Outcomesmentioning
confidence: 99%
“…The authors concluded that using GBS ≤ 2 and age of less than 70 years to define lowrisk patients allows 10.5% of patients suffering from UGIB to be safely managed in the community. Over a 5-year period of managing such patients without hospital admission, McLaughlin et al [43] showed that any of them required endoscopic intervention, blood transfusion or surgery, and that the 28 d mortality was nil. A recent multicentre Danish study reported that a GBS cut-off value of ≤ 1 and an age modified low-risk version can be safely and effectively used to reduce unnecessary admissions for suspected UGIB [55] .…”
Section: The Importance Of Outcomesmentioning
confidence: 99%